Biblical reasoning: christological and trinitarian rules for exegesis - Jamieson, Bobby (Baker Academic, 2022)
Two experts in exegesis and dogmatics show how Christology and the doctrine of the Trinity are grounded in Scripture and how knowledge of these topics is critical for exegesis.